A Study on Socio- Economic Conditions on Menstrual Hygiene Management of Adolescent Girls: Exploring the Impact of Socio-Economic Conditions on Menstrual Hygiene Management of Adolescent Girls (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Menstrual hygiene, as well as proper perception and belief, will protect women from suffering. The majority of women learn about menstruation and menstrual hygiene from their mothers, sisters, and aunts. Only a few people learn the correct information from teachers or health professionals. Infections of the reproductive tract and their consequences can be avoided with better knowledge and safe menstrual practices. The ideal menstrual health education program would encourage students to consider the connections between knowledge, behavior, and improved human health. It would also assist in the improvement of maternal health.